CAREERS IN THEORY AND EXPERIENCE (Authors: Warren Gribbons and Paul R. Lohnes) - Mendelson, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1983)
Warren Gribbons and Paul R. Lohnes. CAREERS IN THEORY AND EXPERIENCE: A twenty-year longitudinal study. New York: State University of New York Press, 1982. 145 pp. $44.50 cloth, $14.95 paper.